Histochemical study of skeletal muscles in experimental spinal cord blunt injury. - Raskaliei, T. Ya.; Raskaliei, V. B.; Shobat, L. B.; Gavriliuk-Skiba, G. O. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Investigation of causes, frequency, clinical manifestations of spinal cord injury is necessary for the correct medical treatment, proper transport to the hospital, effective rehabilitation of the patient. Objective. To provide morphological characteristics of the adaptive capacities of skeletal muscle tissue in a neurotrophic violations of the spinal cord control after spinal cord injury. Methods. Under the influence of thiopental anesthesia laminectomia was performed with the following blunt trauma of the spinal cord using a "Device for modeling of the blunt tram of the spinal cord". The experimental animals (10 white laboratory rats) were divided into 2 groups. Histochemical study of the quadriceps and tibial muscles of hind rat limbs was performed. Results. In 1 hour after blunt injury next changes were documented: in skeletal muscle – dilatation of interstitial space between myosymplasts by swelling; lack of active movement in the skeletal muscle of the lower extremities by blocking the conduction of nervous impulses in nerve fibers; histochemical changes manifested in the form of migration of PAS-positive component of the sarcolemma in the interstitial space by increasing the permeability of the sarcolemma, reducing the activity of ATPase, increased acid phosphatase and accumulation of lactate dehydrogenase in the sarcolemma, confirming manifestation of degenerative changes in the myosymplast. Conclusion. Even short-term violation of the innervation of skeletal muscles leads to quick disruption of biochemical processes.